Worldwide cancer statistics of adults over 75 years old in 2019: a systematic analysis of the global burden of disease study 2019 - Danhong Xiang; Shiwei Hu; Tianxiang Mai; Xinlu Zhang; Lan Zhang; Shengjie Wang; Keyi Jin; Jian Huang (BMC, 2022)
Abstract Background and purpose Cancer has become one of the major killers of humanity due to the number of people over the age of 75 increasing with population ageing. The aim of this study was to analyse the incidence and mortality rates in people over 75 of 29 cancer types in 204 countries and regions, as well as the trends from 1990 to 2019. Methods Twenty-nine cancer types were collected from the Global Burden of Disease (GBD) 2019 database( https://vizhub.healthdata.org/gbd-results/ ). We collected global cancer data for 2019 in terms of sex, age, sociodemographic index (SDI), region, etc. The estimated annual percentage change (EAPC) was calculated to assess the trend of the cancer incidence and mortality rate from 1990 to 2019. Results In 2019, the number of new cancer cases and deaths among people 75 and older was almost 3 and 4.5 times that of 1990, respectively. From 1990 to 2019, there was a slow rise in incidence and a slight decline in mortality. There were significant differences in the cancer burden based on sex, age, region, and SDI. The cancer burden in men was higher than in women. In addition, the cancer burden varied from region to region. The highest cancer burden occurred in high-income North America. In addition, the higher the SDI was, the greater the burden of cancer. The incidence of cancer in high SDI was approximately seven times that of low SDI, and the trend of increase in high SDI was obvious. However, the trend of mortality in high SDI was decreasing, while it was increasing in low SDI. Conclusions The present study focused on the cancer burden in adults over 75 years old. The findings in the study could serve as the basis for an analysis of the types of cancers that are most prevalent in different regions. This is beneficial for strategies of prevention and treatment according to the characteristics of different countries and regions to reduce the burden of cancer in older adults.